Local Cultural Wisdom in Waste Handling and Supporting Creative Industries - Hudi Setyobakti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Local cultural values ​​are often an alternative solution in solving problems in society. Including social and environmental problems including waste. The purpose of this study is to conduct an assessment of the problem and alternative solutions to the waste problem at village tourism sites based on local culture and potential. The method used qualitatively with interviews. The results obtained are that there is a pattern of approach to handling waste problems by utilizing the potential of banana plants, namely banana stems to become a creative industry as a substitute for environmentally friendly places to eat and drink.